Beneficial effects of SGLT2 inhibitor on metabolic inflexibility and visceral fat amount in animal model of obese type 2 diabetes - Kento Hara; Yusuke Sakai; Yuji Tajiri; Masatoshi Nomura (Heliyon, 2022)
Background: Obesity and type 2 diabetes mellitus (T2DM) are often accompanied with a disrupted diurnal rhythm of eating and sustained anabolic state, leading to metabolic inflexibility. In the present study, we plan to investigate effects of a sodium glucose co-transporter 2 (SGLT2) inhibitor, canagliflozin (CANA), on such a metabolic inflexibility, especially on fat metabolism, in the obese type 2 diabetic rats. Materials and methods: Five-week-old male SDT (Spontaneously Diabetic Torii) fatty rats as a model of obesity and T2DM and Sprague-Dawley (SD) rats were treated by either CANA (10 mg/kg) or saline (vehicle) orally for 14 days. Then, after the measurement of respiratory quotient (RQ) and visceral and subcutaneous fat volumes, rats were euthanized and blood and tissue samples were collected. Results: The treatment by CANA significantly enhanced β-ketone concentration in the blood during light period in the SDT fatty rats with no effect on blood glucose concentration. The CANA treatment significantly reduced visceral fat volume in the SDT fatty rats. A diurnal rhythm of RQ was severely disrupted and persistently high throughout the day in the vehicle-treated SDT fatty rats. By the administration of CANA clearly restored the disrupted diurnal rhythm of RQ with a revival of the nadir during light period. Quantitative real-time RT-PCR revealed a significant increase of AMP-activated protein kinase and decrease of acetyl-CoA carboxylase-1 expression in the liver, and a significant increase of hormone sensitive lipase and uncoupling protein-2 expression in the white adipose tissue by the treatment of CANA in the SDT fatty rats. Conclusion: CANA as a SGLT2i reduced visceral fat amount via the enhancement of fat oxidation during the light period, leading to an amelioration of metabolic inflexibility in an obese diabetic model. A novel mechanism of CANA prompts the possibility that this new class of anti-diabetic agent could be a promising anti-obesity agent as well.